The Cross-Provincial Data of Life Expectancy Effect on Pension Fund in Indonesia - Ridho, Sari Lestari Zainal; Sabli, Habsah Binti Haji Mohamad; Setiawan, Heri (Universitas Pendidikan Ganesha, 2021)
The data presented in this research is an observational cross-province study of life expectancy and pension funds. The data were extracted from the published database of Statistic Indonesia and Indonesia Financial Services Authority, covering a period of 2015 to 2019. The collected data were analyzed; using a panel data regression model on random effect assumptions with Generalized Least Squares. The finding of this research shows that there is a positive and significant effect of life expectancy on pension funds. This research paper data will assist in promoting the opportunity for pensions fund business or institution.